1978
DOI: 10.1093/oxfordjournals.jbchem.a131942
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolites of Polyamines in Rats

Abstract: Urinary metabolites of polyamines in rats were studied systematically by the intraperitoneal injection of radioactive polyamines. Urinary metabolites were fractionated into 4 fractions containing non-polar and acidic compounds, acidic and neutral ampholytes, basic ampholytes and polyamines. A large amount of radioactivity was detected in the fractions containing non-polar and acidic compounds and polyamines of urine of rats injected with radioactive putrescine, while in the case of the injection of radioactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The physiological function of 2-hydroxyputrescine has not been studied in living things, and it is difficult to discuss such functions of this compound in the CNS. However, we can compare the concentration of this compound to that of putrescine, its precursor (Noto et al, 1978), in some areas of the CNS. In the cerebellum, the concentration of 2-hydroxyputrescine is very high, but that of putrescine is very low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological function of 2-hydroxyputrescine has not been studied in living things, and it is difficult to discuss such functions of this compound in the CNS. However, we can compare the concentration of this compound to that of putrescine, its precursor (Noto et al, 1978), in some areas of the CNS. In the cerebellum, the concentration of 2-hydroxyputrescine is very high, but that of putrescine is very low.…”
Section: Discussionmentioning
confidence: 99%
“…Putrescine is metabolized into y-aminobutyric acid (GABA) by amine oxidase (EC 1.4.3.6) in mammalian organs (Tsuji and Nakajima, 1978), and the release of GABA formed from putrescine in the CNS is enhanced by high levels of potassium . Putrescine is also metabolized in the rat into 2-hydroxyputrescine (Noto et al, 1978), which has been already isolated and identified in Psezrdutnonas cells (Tobari and Tchen,197 1). 2-Hydroxyputrescine from bovine brain has been characterized (Hasegawa et al, 1986).…”
mentioning
confidence: 95%
“…Under these conditions GABA and putrescine moved about 8 and 20 cm from the origin to the cathode, respectively. These column and paper electrophoretic procedures were previously reported by Noto et al (1978). GABA was visualized with 0.2% ninhydrin in acetone.…”
Section: Methodsmentioning
confidence: 99%
“…3 paper by using different solvents: a, propan-2-ol/85% (v/v) formic acid/water (8: 1: 1, by vol.) (Noto et al, 1978;Kakimoto et al, 1969); b, propan-1-ol/triethylamine/water (85:3:15, by vol.) (Dubin & Rosenthal, 1960).…”
Section: Methodsmentioning
confidence: 99%